Exploring the Role of Pictograms in the Comprehension of Pain - Merks P; Vaillancourt R; Dulai I; Lamontagne G; Pinkas J; Religioni U; Świetlik D; Kaźmierczak J; Blicharska E; Zender M; Cameron J (Journal of Pain Research, 2023)
Piotr Merks,1 Regis Vaillancourt,2 Irene Dulai,2 Gloria Lamontagne,3 Jarosław Pinkas,4 Urszula Religioni,4 Dariusz Świetlik,5 Justyna Kaźmierczak,6 Eliza Blicharska,7 Mike Zender,8 Jameason Cameron2 1Department of Pharmacology and Clinical Pharmacology, Faculty of Medicine, Collegium Medicum, Cardinal Stefan Wyszyński University in Warsaw, Warsaw, Poland; 2Pharmacy Department, Children’s Hospital of Eastern Ontario, Ottawa, Ontario, Canada; 3Biomedical Sciences Faculty, University of Ottawa, Ottawa, Ontario, Canada; 4School of Public Health, Centre of Postgraduate Medical Education of Warsaw, Warsaw, Poland; 5Department of Biostatistics and Neural Networks, Medical University of Gdansk, Gdansk, Poland; 6Zdrowit Sp. Z O.o, Pharmacy Chain, Piekary Śląskie, Poland; 7Department of Pathobiochemistry and Interdisciplinary Applications of Ion Chromatography, Medical University of Lublin, Lublin, Poland; 8School of Design, University of Cincinnati, Cincinnati, OH, USACorrespondence: Urszula Religioni, School of Public Health, Centre of Postgraduate Medical Education of Warsaw, Kleczewska 61/63, Warsaw, 01-826, Poland, Tel +48225693700, Email urszula.religioni@gmail.comIntroduction: Pain is both difficult to see and to articulate and this is challenging for both patients and clinicians. The aim of this study was to develop and test pictograms to describe different pain qualities.Methods: 22 pictograms were developed for evaluation based on pain qualities of the short form McGill Pain Questionnaire, version 2 (SF-MPQ-2). An online matching survey was conducted and disseminated via social media in 2021.Results: An overall matching of 66% or higher between pictogram and pain qualities descriptors was considered a proper matching. This study was carried out internationally (males = 57, age=41y.o. ± 16; females = 155, age=41y.o.± 17) and in Poland (males=49, age =35y.o.± 17; females = 164, age=35y.o.± 16). There were 14 pictograms that did not achieve 66% matching in any country. 8 pictograms mutually in all subgroups achieved a matching score of ≥ 66% regardless of geographic location, sex, income, or education level.Discussion and Conclusions: These 8 pictograms can be used clinically once they have been redrawn to improve consistency, and future research in the design of pictograms representing pain qualities of the SF-MPQ-2 should focus on design improvements for the remaining 14 pain qualities with poor comprehensibility.Keywords: pain, pictograms, health literacy, SF-MPQ-2, pain comprehension